The response of sexual and stress hormones of male pro-cyclists during continuous intense competition - Fernandez-Garcia, B.; Lucia, A.; Hoyos, J.; Chicharro, J. L.; Rodriguez-Alonso, M.; Bandres, F.; Terrados, N. (International Journal of Sports Medicine, 2002)
The aim of this study was to compare hormonal changes in plasma total testosterone (T), cortisol (C), luteinizing hormone (LH), follicle-stimulating hormone (FSH) and prolactin (P) in two world-class teams, both consisting of 9 top male pro-cyclists, during a real sports situation (the 1998 "Vuelta a Espana", a 3-week multi-stage international cycling competition). Venous blood samples were taken the day before the race (S0), after 1 week (S1), after 2 weeks (S2) and at the end of the race (S3). The S0 T level was significantly lower in the team with more racing days in the previous month. There was a significant basal T decrease (p < 0.05) during the race in comparison with the initial value, in spite of the difference in S0 T level between teams. However, there was no difference between teams in the mean decrease in T level. C decreased significantly between S0 and S1 and between S1 and S2, but not between S2 and S3. There were no differences in P concentration between teams or throughout the study, except for a significant increase between S2 and S3. There were no initial differences in LH nor FSH concentration between the teams, nor at any of the study follow-up times. We conclude that in professional top-level athletes S0 T values depend on the number of competition days of the previous month. We observed a similar decrease in the T levels in both teams, independent of the absolute S0 values. In both teams C decreased during long-lasting cycling competition.